The Effect of Work-Family Conflict, Communication Pattern, Social Support, and Stress Levels toward Family Quality of Life During The Covid-19 Pandemic: The Effect of Work-Family Conflict, Communication Pattern, Social Support, and Stress Levels toward Family Quality of Life During The Covid-19 Pandemic - Hanum Fauziah Ramadhanti; Megawati Simanjuntak; Irni Rahmayani Johan (Journal of Family Sciences, 2022)
Staying at home during the pandemic COVID-19 should be an opportunity to improve the family's quality of life (QoL). Positively, gathering with family at home provides an opportunity to get to know family members in-depth, but also prone to causing various frictions due to the boundary between office work, housework, and family becoming invisible. This study aims to analyze the effect of work-family conflict, communication patterns, social support, and stress levels on the family quality of life before and during the COVID-19 pandemic. The design of this study was a retrospective and cross-sectional study. The study was conducted on nuclear families with working mothers in Jabodetabek and involved 169 working mothers as respondents using voluntary sampling. This study used descriptive analysis, paired two-group analysis, and path analysis. As a result, work-family conflict, communication patterns, social support, stress levels, and quality of life increased during the pandemic. The results of the path analysis found that work-family conflict, communication patterns, and social support had a significant direct effect on family quality of life during a pandemic. The quality of life can be improved by increasing open communication patterns, more social support from husbands and extended families, and reducing work-family conflicts.